Serotonergic Control of Metabolic Homeostasis - Wyler, Steven C.; Lord, Caleb C.; Lee, Syann; Elmquist, Joel K.; Liu, Chen (Frontiers in Cellular Neuroscience, 2017)
New treatments are urgently needed to address the current epidemic of obesity and diabetes. Recent studies have highlighted multiple pathways whereby serotonin (5-HT) modulates energy homeostasis, leading to a renewed interest in the identification of 5-HT-based therapies for metabolic disease. This review aims to synthesize pharmacological and genetic studies that have found diverse functions of both central and peripheral 5-HT in the control of food intake, thermogenesis, and glucose and lipid metabolism. We also discuss the potential benefits of targeting the 5-HT system to combat metabolic disease.